Desempenho de gotejadores usando efluente de esgoto tratado para irrigação - Fischer Filho, João Alberto [UNESP] (2015)
The use of low-quality effluent in drip irrigation can cause flow variation of the emitters and compromising the efficiency of irrigation. This study aimed to evaluate the flow variation of emitters in irrigation system using treated sewage effluent (TSE). A drip irrigation system with ten types of emitters was installed at FCAV/UNESP, with the TSE coming from the Sewage Treatment plant by Jaboticabal-SP, filtered through a disc filter (120 mesh). Seven evaluations of flow rate drippers were performed (0, 100, 200, 300, 400, 500 and 600 hours of operation) operating at 100 kPa. The experimental was randomized in a factorial arrangement 4x7 (4 self compensating emitters, know as G, and 7 times) and 6x7 (6 not self compensating emitters, know as E, and 7 times) with four replications and Tukey's test to compare means. The relative flow rate (Qr), the flow rate coefficient of variation (CVQ) and degree of blockage (GE) were determined. The drippers study showed average to good uniformity due in function of the manufacturing variation coefficient, and drippers not self compensating showed excellent coefficient of determination, characterized as turbulent flow. It was found that the model self compensating emitters were less susceptible to clogging and non self compensating models were more susceptible to clogging during system functioning. The G4 model showed better performance compared to the other models self compensating emitters and the E1 model stood out among non self compensating emitters, presenting Qr close to 100%, low CVQ and GE values. The results obtained allow to state that the TSE usage time affects the flow of the drippers